2010
DOI: 10.1063/1.3429226
|View full text |Cite
|
Sign up to set email alerts
|

Persistent template effect in InAs/GaAs quantum dot bilayers

Abstract: The dependence of the optical properties of InAs/GaAs quantum dot ͑QD͒ bilayers on seed layer growth temperature and second layer InAs coverage is investigated. As the seed layer growth temperature is increased, a low density of large QDs is obtained. This results in a concomitant increase in dot size in the second layer, which extends their emission wavelength, reaching a saturation value of around 1400 nm at room temperature for GaAs-capped bilayers. Capping the second dot layer with InGaAs results in a furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…However, in large aspect ratio quantum dots (AR > 0. 25), the hole confinement is significantly modified compared with that in lower AR dots-this modified confinement is manifest in the interfacial confinement of holes in the system. Since the contributions to the ground state optical intensity (GSOI) are dominated by lower-lying valence states, we therefore propose that the room temperature GSOI be a cumulative sum of optical transitions from multiple valence states.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…However, in large aspect ratio quantum dots (AR > 0. 25), the hole confinement is significantly modified compared with that in lower AR dots-this modified confinement is manifest in the interfacial confinement of holes in the system. Since the contributions to the ground state optical intensity (GSOI) are dominated by lower-lying valence states, we therefore propose that the room temperature GSOI be a cumulative sum of optical transitions from multiple valence states.…”
mentioning
confidence: 90%
“…Past experimental studies have shown that the size of the QDs increases with the stacking number 12,25,26 in multilayer QD stacks. Thus, the aspect ratio AR of the QDs in upper layers may increase above 0.3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The QD bilayers comprise two closely-stacked QD layers, separated by 10 nm GaAs: a seed layer that determines the overall QD density and an upper layer, for which the growth conditions can then be chosen to provide a significant extension in the emission wavelength. The two QD layers are sufficiently close together to allow efficient carrier transfer from the seed layer to the upper layer, such that emission from the seed layer is suppressed and device operation is determined by the upper layer QDs [7,8]. The active region is an undoped 500 nm thick layer of GaAs containing three QD bilayers separated by 50 nm bounded by n and p-doped 1500 nm thick Al 0.33 Ga 0.67 As cladding layers.…”
Section: Sample Detailsmentioning
confidence: 99%
“…It would therefore be particularly valuable to have sources that emit at wavelengths in the telecommunication bands (1.3 or 1.55 μm), as these have notably lower levels of attenuation through optical fibres. It is possible to fabricate QDs in a GaAs spacer layer, either as high-density ensembles for room temperature operation or as single-emitters at low temperature, that emit at 1.3 μm wavelengths [6], [7]. Another challenge is that QDs emit isotropically and are incorporated in high refractive index materials, which makes efficient photon extraction difficult [8].…”
Section: Introductionmentioning
confidence: 99%